Integrated CT–Fluoroscopy Equipment: Improving the Interventional Radiology Approach and Patient Experience for Treatment of Musculoskeletal Malignancies - Yevich, Steven; Odisio, Bruno C.; Sheth, Rahul; Tselikas, Lambros; de Baère, Thierry; Deschamps, Frederic (Seminars in Interventional Radiology, 2018)
Integrated CT–fluoroscopy equipment augments the comprehensive approach to the treatment of musculoskeletal (MSK) malignancy by interventional radiology techniques. As the role of minimally invasive treatment expands to meet the highly variable presentation of MSK malignancy, creative solutions to treatment challenges are required to improve locoregional tumor control and durability of pain palliation. Challenges to effective treatment can often be attributed to a combination of aggressive tumor biology, large size, forbidding location, and adverse vascularity. In these cases, a tailored treatment approach may necessitate the application of multiple interventional radiology (IR) techniques that require different image guidance capabilities. Integrated CT–fluoroscopy equipment provides the means to leverage both imaging modalities within the same procedural setting to facilitate the simultaneous application of multiple synergistic treatments and protective measures. This article examines the potential role of hybrid units in the IR treatment of challenging MSK malignancies as a means to empower a paradigm transition for a more comprehensive and patient-tailored approach.
Keywords: integrated; hybrid; musculoskeletal; malignancy; interventional radiology